Implementasi Pelayanan Pengaduan Masyarakat di Sentra Pelayanan Kepolisian Polsek Penukal Abab - Venny Delviari; Sawitri Budi Utami; Edah Jubaedah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research was conducted to provide an overview of public complaint handling implementation at the Service Desk (SPK) of Penukal Abab Police Sector, using a qualitative approach. The informants in this study included the head of the SPK at Penukal Abab Police Sector and members of the community who filed police reports. Data analysis techniques involved data collection, data reduction, data display, and drawing conclusions. From the research conducted by the researcher, it was found that the community members who can file complaints at SPK Penukal Abab come from the Penukal and Abab Districts. The efficiency factors hindering public complaint services at SPK Penukal Abab include a lack of human resources, specifically officers handling public complaints at SPK Penukal Abab. The limited number of officers combined with a high volume of reports places a heavy workload on existing personnel, leading to suboptimal performance. Efforts that can be undertaken by SPK officers at Penukal Abab Police Sector to enhance the quality of public complaint services were also explored.